Seaweed Biomaterials 2018
DOI: 10.5772/intechopen.77051
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia (Oreochromis aureus) Collagen for Medical Biomaterials

Abstract: Collagen is a natural polymer widely used in pharmaceutical products and nutritional supplement due to its biocompatibility and biodegradability. Collagen is a fibrous protein that supports various tissues, and its primary structure is formed by repeated units of glycineproline-hydroxyproline. Traditional sources of collagen, such as bovine and pig skins or chicken waste, limit their use due to the dangers of animal-borne diseases. Thus, marine animals are an alternative for the extraction of collagen. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 70 publications
2
9
0
2
Order By: Relevance
“…FTIR analysis confirmed that the carbon rich layer we found with the EDS is composed by organic residues particularly the C-H stretch and v(C=O) peaks around 2931 and 1737 respectively (Fig. 5A), which are commonly found in collagen I (Belbachir et al 2009;Jeevithan et al 2014;Valenzuela-Rojo et al 2018) and keratin (Chandini et al 2017;Estévez-Martínez et al 2013); highly abundant proteins found in the scales and skin of fishes (Bhagwat & Dandge 2016;Elliott 2011). Amide A, I, II, and III, C-H stretch and v(C=O) peaks were clearly observed in the FTIR of the extant Orechromis sp.…”
Section: Sem-eds Resultssupporting
confidence: 66%
“…FTIR analysis confirmed that the carbon rich layer we found with the EDS is composed by organic residues particularly the C-H stretch and v(C=O) peaks around 2931 and 1737 respectively (Fig. 5A), which are commonly found in collagen I (Belbachir et al 2009;Jeevithan et al 2014;Valenzuela-Rojo et al 2018) and keratin (Chandini et al 2017;Estévez-Martínez et al 2013); highly abundant proteins found in the scales and skin of fishes (Bhagwat & Dandge 2016;Elliott 2011). Amide A, I, II, and III, C-H stretch and v(C=O) peaks were clearly observed in the FTIR of the extant Orechromis sp.…”
Section: Sem-eds Resultssupporting
confidence: 66%
“…FTIR analysis confirmed that the carbon rich layer we found with the EDS is composed of, organic residues, particularly the C-H stretch and v(C=O) peaks around 2,931 and 1,737 respectively (Fig. 5A), which are commonly found in collagen I (Belbachir et al, 2009;Jeevithan et al, 2014;Valenzuela-Rojo, López-Cervantes & Sánchez-Machado, 2018) and keratin (Chandini et al, 2017;Estévez-Martínez et al, 2013); highly abundant proteins found in the scales and skin of fishes (Bhagwat & Dandge, 2016;Elliott, 2011). Amide A, I, II, and III, C-H stretch and v(C=O) peaks were clearly observed in the FTIR of the extant Orechromis sp.…”
Section: Systematic Paleontologysupporting
confidence: 66%
“…A higher Td indicates a stronger bonding within the collagen triple helix chains. Fish collagen is known to have lower Td than mammalian sources [ 31 ], so the increase of Td is desirable for most tissue engineering applications.…”
Section: Resultsmentioning
confidence: 99%
“…After that, it was rinsed thoroughly with deionized water. Fat contents were removed using ethanol: acetone 1:1 mixture as described by [ 31 ]. Afterward, the skins were exhaustively washed with deionized water to prepare for collagen extraction.…”
Section: Methodsmentioning
confidence: 99%